2015
DOI: 10.1039/c5sc00929d
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-catalysed asymmetric hydrovinylation of 1,3-dienes

Abstract: Excellent selectivity with complexes of DIOP, BDPP and Josiphos with E-1,3-dienes reacting faster than the Z-isomers at low temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 111 publications
(159 reference statements)
1
34
0
Order By: Relevance
“…6 In 2015, RajanBabu reported full details of the development of (asymmetric) 1,4-hydrovinylation of linear 1,3dienes, including the effect of promoters, the screening of achiral and chiral ligands, and the scope of both the racemic and enantioselective reactions. 7 For the enantioselective reaction, the broadest scope was achieved using (DIOP)CoCl 2 as the precatalyst and Me 3 Al or methylaluminoxane (MAO) as the activator, converting various alkyl-substituted 1,3dienes 1 into the chiral 1,4-hydrovinylation products 2 with Z-configuration (Scheme 1a). Other diphosphine ligands such as BDPP could also be used.…”
Section: Hydrovinylationmentioning
confidence: 99%
“…6 In 2015, RajanBabu reported full details of the development of (asymmetric) 1,4-hydrovinylation of linear 1,3dienes, including the effect of promoters, the screening of achiral and chiral ligands, and the scope of both the racemic and enantioselective reactions. 7 For the enantioselective reaction, the broadest scope was achieved using (DIOP)CoCl 2 as the precatalyst and Me 3 Al or methylaluminoxane (MAO) as the activator, converting various alkyl-substituted 1,3dienes 1 into the chiral 1,4-hydrovinylation products 2 with Z-configuration (Scheme 1a). Other diphosphine ligands such as BDPP could also be used.…”
Section: Hydrovinylationmentioning
confidence: 99%
“…Early investigations with prototypical enynes 1a and 1b revealed that the ligands (Fig. 3 D ) we had successfully used in several other cobalt-catalyzed reactions,( 35 ) while giving high yields and excellent E : Z ratios of the products, gave unacceptable enantioselectivities (Table S3, entries 1-14). These included bis -diphenylphosphino-ligands ( S,S )-BDPP ( L1 ), ( S,S )-DIOP ( L2 ) and JOSIPHOS ( L3a and L3b ), BINAP and the bis -phospholane ligand L4 (Fig.…”
mentioning
confidence: 99%
“…3 D ). After an extensive search,( 35 ) we identified CoCl 2 -complexes of phosphinooxazoline ligands (e.g., L8-L9 )( 36 ) as the most suitable catalysts for this tandem sequence(Tables S3 and S4). Among the activators Et 2 AlCl was found to be the most general (Table S4), often giving significantly better enantioselectivities than TMA which was used in initial screening studies.…”
mentioning
confidence: 99%
See 2 more Smart Citations